Neuroinflammation and stress-induced pathophysiology in major depressive disorder: mechanisms and therapeutic implications - Zhao, Kunying; Zhang, Yuxiao; Yang, Shuda; Xiang, Lirong; Wu, Shangpeng; Dong, Junfang; Li, Huan; Yu, Haofei; Hu, Weiyan (Frontiers in Cellular Neuroscience, 2025)
Major depressive disorder (MDD) is one of the most common mental health conditions, characterized by pervasive and persistent low mood, low self-esteem, and a loss of interest or pleasure in activities that are typically enjoyable. Despite decades of research into the etiology and pathophysiological mechanisms of depression, the therapeutic outcomes for many individuals remain less than expected. A promising new area of research focuses on stress-induced neuroinflammatory processes, such as the excessive activation and crosstalk of microglia and astrocytes in the central nervous system under stress, as well as elevated levels of pro-inflammatory cytokines, which are closely linked to the onset and progression of depression. This review summarizes the mechanisms through which neuroinflammation induces or promotes the development of depression, and also highlights the effective roles of small molecules with anti-inflammatory activity in the treatment of MDD. Understanding the specific mechanisms through which stress-induced neuroinflammation further impacts depression, and using technologies such as single-cell RNA sequencing to elucidate the specific subtypes and interactions of microglia and astrocytes in depression, is of great importance for developing more effective therapeutic strategies for MDD.